Fabrication and mechanical properties of carbon fiber/epoxy nanocomposites containing high loadings of noncovalently functionalized graphene nanoplatelets. (26th May 2020) - Kim, Joonhui; Cha, Jaemin; Chung, Bongjin; Ryu, Seongwoo; Hong, Soon H.
Abstract: Carbon fiber-reinforced polymer (CFRP) composites containing graphene nanoplatelets (GNPs) were prepared and characterized. Bonding via π−π interactions with poly(4-aminostyrene) (PAS) improved the degree of dispersion of the GNPs in an epoxy matrix. Differences in dispersion and reinforcement between pristine GNPs and PAS-GNPs were established by ultraviolet–visible spectroscopy and scanning electron microscopy. The PAS-GNP/epoxy nanocomposites were characterized by their fracture toughness. The results were discussed in terms of the dispersion quality of the GNPs. Furthermore, the PAS-GNP/epoxy nanocomposites were applied to carbon fiber fabric and the interlaminar shear strength (ILSS) and fracture toughness were measured. The greatest improvements in ILSS (252%) and fracture toughness (142%) were obtained with 4 wt% PAS-GNPs. The superior mechanical properties of the CF/PAS-GNP/epoxy nanocomposites are attributed to better filler dispersion and crack bridging.